Investigation of the shared biological mechanisms and common biomarker APTAF1 of sleep deprivation and mild cognitive impairment using integrated bioinformatics analysis - Liu, Xiaolan; Lu, Baili; Huang, Hui (Frontiers in Pharmacology, 2024)
The relationship between sleep loss and cognitive impairment has been widely recognized; however, the underlying mechanisms and potential biomarkers remain poorly understood. This study aimed to explore the shared biological mechanisms and common biomarkers of sleep loss and cognitive impairment. We investigated the association between sleep deprivation (SD) and mild cognitive impairment (MCI) using data from the Gene Expression Omnibus database. A total of 32 mitochondrial-related differentially expressed genes were identified in the SD and MCI groups. GO analysis indicated that these genes were significantly enriched in mitochondrial transport, and KEGG analysis showed that they were mainly involved in pathways of neurodegenerative diseases. In addition, ATPAF1, whose expression was significantly down-regulated in both SD and MCI, was identified using machine learning algorithms as a common biomarker with favorable diagnostic performance. GSEA and GSVA revealed that ATPAF1 was mainly involved in metabolic pathways, such as oxidative phosphorylation; acetylcholine metabolic process; and valine, leucine and isoleucine degradation. Immune infiltration analysis showed that the expression of ATPAF1 was correlated with changes in immune cells, especially key immune cell types associated with SD and MCI. To the best of our knowledge, this study is the first to reveal that mitochondrial dysfunction is a common pathogenesis of sleep loss and MCI and present ATPAF1 as a possible biomarker and therapeutic target in SD and MCI.